Entropy-driven formation of chiral nematic phases by computer simulations - Simone Dussi (Nature Portfolio, 2016)
The entropy-driven formation of cholesteric liquid crystal, one of the widely used liquid crystal phase, has not yet been addressed in simulations due to large unit cells. Here, Dussi and Dijkstra overcome this problem by introducing a hard-particle model and show that shape alone can stabilize a chiral nematic phase.